Silver-decorated, light-activatable polymeric antimicrobials for combined chemo-photodynamic therapy of drug-resistant bacterial infection. (7th October 2020) - Hou, Xiaoxue; Yang, Lijun; Liu, Jinjian; Zhang, Yumin; Chu, Liping; Ren, Chunyan; Huang, Fan; Liu, Jianfeng
Abstract : In this article, we describe a silver-decorated, light-activatable polymeric antimicrobial with strong synergistic chemo-photodynamic effect to combat bacterial infections. Abstract : Drug-resistant bacterial infections have stolen the spotlight in recent years as stubborn diseases intimidating public health, thus urgently requiring the development of innovative treatment strategies with high antibacterial efficiency and low bacterial resistance. Here, a polymeric antimicrobial with synergistic chemo-photodynamic therapy function is fabricated to combat drug-resistant bacterial infections. In this strategy, polymeric micelles based on amphiphilic poly(aspartic acid)- block -poly(ε-caprolactone) (PAsp- b -PCL) are used as nanocarriers to encapsulate a photosensitizer protoporphyrin IX (PpIX) in the micellar core, which then undergo silver nanoparticle decoration on the micellar shell through an in situ reduction method. Compared with mono-therapy, the combination of silver nanoparticle decoration and light-activatable PpIX enables the resulting polymeric antimicrobial to exert chemo-photodynamic activity to kill drug-resistant bacteria more potently in vitro . Furthermore, the prepared polymeric antimicrobials with synergistic antibacterial activity show robust eradication efficacy against subcutaneous infections induced by drug-resistant Staphylococcus aureus in a murine model. Therefore, our study provides a simple and potent strategy to realize combination therapy for eradicating drug-resistant bacterial infections.